2D MODELING OF OVERLAND FLOW DUE TO TSUNAMI WAVE PROPAGATION - Bagus Adityawan (NIM 250 05 045), Mohammad
Abstract : Tsunami wave is caused by vertical deformation of water. The deformation can be caused by earthquake, volcano eruption, avalanche and meteor which fall in to the sea. Tsunami can be categorized as long wave. Tsunami wave length is hundreds of kilometer with +/- 1 meter amplitude when it propagates at the deep sea. This type of wave usually propagates at the speed of +/- 30-1000 km/hour, with 5-90 minutes periode. Tsunami wave propagation can be categorized in two zones. The first zone is assigned to the condition where the propagation is dominated by wave and the second zone is assigned to the condition where the propagation is similar to flood. The transition between the two zones is the result from shoaling and wave run up process. As the wave approaches shoreline, shoaling will caused the wave to loose its energy. The amplitude of the wave will grow along with the shortened of its length. The inundation is mainly determined by the run up height and bottom friction. The flow in this area will also be highly affected by debris, which is neglected in this study. The model is developed for tsunami wave propagation from shallow water to land. Parameters which affected the wave propagation are; wave height; periode; wave length and direction of incoming wave; topography and bathimetery; landcover; normal water level/depth. The model is developed with two gouverning equition. The first model is developed from the full dynamic St.Venant equation and the second one is developed from the standard Boussinesq equation. The St.Venant equation is solved using Mac Cormack numerical scheme, while the Boussinesq equation is solved using the Adam Bashford scheme. The wet/dry condition is applied to the St.Venant model by giving a minimum depth for the model. When the depth drop bellow the minimum depth, the water depth and velocity is given zero value. The Boussinesq model does not accommodate wet/dry treatment. Dirichlet boundary condition is applied for water depth and velocity parallel to the axis. Exrapolation is used for velocity perpendicular to the axis. Incoming wave is given as a sea boundary condition. The bottom friction in the St.Venant model is modeled as the manning coefficient. Zero value is applied to the sea domain. Caustic wave often causes instability of the model, especially when modeling complex topography and bathimetry. Numerical filter is applied to the model to overcome this problem. Both model are used to simulate wave propagation at a achannel with no slope. The travel time of the wave acquired from both of the model shows no significant difference. However, the wave obtained from the St.Venant model is showing faster decay compare to the Boussinesq model. This is caused by the dissipation terms in the Boussinesq model. The real time for simulating the Boussinesq model is twice longer than the St.Venant model. Simulation for run up over a sloping beach with the St. Venant model shows good comparison with eksperimental data and other numerical models. A good comparison is also found for simulation where the wave hit a verticall wall which correspond to the reflecting wave theory. The St. Venant model is used to simulate the Tsunami 2004, Aceh. The topography and grids for the model is obtained by using GIS. The incoming wave uses the measurement data from Mercator ship which is measured at the sea of Thailand when the 2004 tsunami hit the Thay coast. This data is used because there is no measurement data for the tsunami in the sea of Aceh. The model inundation result does not show good comparison with the inundation data measured because the incoming wave used can not represent the incoming wave in Aceh. Froude analyse from the result shows that the incoming wave is normally can be categorized as zone 1 (froude number is less than 1). The maximum distance from shore line where this zone occure is approximately 4 kms towards land. After it reach the maximum distance, the wave can be categorized as zone 2. The breaking wave mechanism which normally occurs is collapsing. It can be concluded from this study that the boundary between the two zone in tsunami wave propagation can be determined from the froude number of the flow.